Relationship between Religiosity and Emotional Maturity with Free Sex Behavior for Students of SMA Negeri Council of Lhokseumawe - Cindy Lola Yolanda; M. Abrar Parinduri; Nur'aini Nur'aini (Budapest International Research and Critics University, 2022)
This study aims to determine the relationship between religiosity and emotional maturity with free sex behavior in SMA Negeri